Evaluating the chemical exfoliation of lithium cobalt oxide using UV-Vis spectroscopy. Issue 11 (20th October 2020) - Pachuta, Kevin; Pentzer, Emily; Sehirlioglu, Alp
Abstract : The exfoliation yield of protonated lithium cobalt oxide was quantified with ultraviolet-vis spectroscopy. An in-depth analysis using this method confirmed and discovered many key aspects of its soft-chemical exfoliation. Abstract : Two-dimensional materials have been at the forefront of chemistry and materials science research for the past decade owing to promising applications across many fields. Improvements in exfoliation processes continually give access to new two-dimensional material compositions, demanding a deeper understanding of the defect structure and exfoliation mechanisms. Chemical exfoliation processes allow for both the fabrication of new, and the production of industrial-scale quantities of two-dimensional materials. For this reason, we report a rapid, efficient, and simple method for evaluating the exfoliation behavior of protonated lithium cobalt oxide. Using a two-step chemical exfoliation method, first by proton–cation exchange, then by treatment with an organo-ammonium hydroxide, the exfoliation yield of lithium cobalt oxide was quantified with a quick and powerful technique, ultraviolet-vis spectroscopy characterization. This method provided an in-depth analysis of the exfoliation of lithium cobalt oxide confirming and discovering many key aspects of its soft-chemical exfoliation relating to layered transition metal oxides. It was determined that the exfoliation yield has a strong dependence on multiple factors, such as the concentration of protons in the powder, the presence of water and hydroxide groups in solution, and the ionic radius and concentration of the intercalating cation. Both morphological changes occurring as a function of reaction conditions and the two-dimensional nature of the final sheets were revealed through scanning electron microscopy and atomic force microscopy. Relative proton concentration of acid-treated lithium cobalt oxide was determined as a function of acid concentration using time of flight secondary ion mass spectrometry after deuterated acid treatment. These experiments led to an improved understanding of the soft-chemical exfoliation of lithium cobalt oxide and can be applied to many layered transition metal oxides.